COVID-19 Signs and Symptom Clusters in Long-Term Care Facility Residents: Data from the GeroCovid Observational Study - Alba Malara; Marianna Noale; Angela Marie Abbatecola; Gilda Borselli; Carmine Cafariello; Stefano Fumagalli; Pietro Gareri; Enrico Mossello; Caterina Trevisan; Stefano Volpato; Fabio Monzani; Alessandra Coin; et al. (Reports, 2022)
Background: Long-term care facility (LTCF) residents often present asymptomatic or paucisymptomatic features of SARS-CoV-2 infection. We aimed at investigating signs/symptoms, including their clustering on SARS-CoV-2 infection and mortality rates associated with SARS-CoV-2 infection in LTCF residents. Methods: This is a cohort study of 586 aged ≥ 60 year-old residents at risk of or affected with COVID-19 enrolled in the GeroCovid LTCF network. COVID-19 signs/symptom clusters were identified using cluster analysis. Cluster analyses associated with SARS-CoV-2 infection and mortality were evaluated using logistic regression and Cox proportional hazard models. Results: Cluster 1 symptoms (delirium, fever, low-grade fever, diarrhea, anorexia, cough, increased respiratory rate, sudden deterioration in health conditions, dyspnea, oxygen saturation, and weakness) affected 39.6% of residents and were associated with PCR swab positivity (OR = 7.21, 95%CI 4.78–10.80; p < 0.001). Cluster 1 symptoms were present in deceased COVID-19 residents. Cluster 2 (increased blood pressure, sphincter incontinence) and cluster 3 (new-onset cognitive impairment) affected 20% and 19.8% of residents, respectively. Cluster 3 symptoms were associated with increased mortality (HR = 5.41, 95%CI 1.56–18.8; p = 0.008), while those of Cluster 2 were not associated with mortality (HR = 0.82, 95%CI 0.26–2.56; p = 730). Conclusions: Our study highlights that delirium, fever, and low-grade fever, alone or in clusters should be considered in identifying and predicting the prognosis of SARS-CoV-2 infection in older LTCF patients.